KARAKTERISTIK PENYADAP AREN DAN PENGARUHNYA TERHADAP JUMLAH PRODUKSI KASUS DI KECAMATAN LEBONG TENGAH – KABUPATEN LEBONG) - Putri, Marthalinda Dwi; Sumantri, Bambang; Asriani, Putri Suci (Jurnal AGRISEP, 2019)
This study aims to determine the characteristics of palm tree tapper and its effect on the amount of sap production. The study was carried out in the Danau Liang Village in Lebong Tengah District, Lebong Regency through a survey involving 45 palm tappers in May 2013. Data collected were characteristics of palm tappers (independent variables) consisting of age, education, experience, family dependents, number tapped trees, and number of trees, and the dependent variable is the production of sap. Data were analyzed descriptively and inferentially using multiple linear regression. The results showed that the average age characteristics of palm tappers were as follows: age 38.24 years, education level was only junior high school level, number of dependents of family of 3 people, experience tapping palm 14.84 years the number of trees tapped 28 stems, age of trees which was intercepted 8.07 years, the number of the widows was 2 pieces, and the length of interception was 1.86 hours. The characteristics of tapping variables that have a significant effect on the amount of sap production are the number of sugar palm trees controlled by tappers and the age of the tapped trees.Keywords: Aren, Tapper Aren, Palm Sugar Palm